The Origin and Evolution of Plastid Genome Downsizing in Southern Hemispheric Cypresses (Cupressaceae) - Sudianto, Edi; Wu, Chung-Shien; Chaw, Shu-Miaw (Frontiers in Plant Science, 2020)
Plastome downsizing is rare in photosynthetic seed plants. However, a large-scale study of five cupressophyte families (conifers II) indicated that the plastomes of some Cupressaceous genera are notably reduced and compact. Here, we enriched taxon sampling in Cupressaceae by adding plastomes of ten previously unreported genera to determine the origin, evolution, and consequences of plastome reduction in this family. We discovered that plastome downsizing is specific to Callitroideae (a Southern Hemispheric subfamily). Their plastomes are the smallest, encode the fewest plastid genes, and contain the fewest GC-end codons among Cupressaceae. We show that repeated tRNA losses and shrinkage of intergenic spacers together contributed to the plastome downsizing in Callitroideae. Moreover, our absolute nucleotide substitution rate analyses suggest relaxed functional constraints in translation-related plastid genes (clpP, infA, rpl, and rps), but not in photosynthesis- or transcription-related ones, of Callitris (the most diverse genus in Callitroideae). We hypothesize that the small and low-GC plastomes of Callitroideae emerged ca. 112–75 million years ago as an adaptation to increased competition with angiosperms on the Gondwana supercontinent. Our findings highlight Callitroideae as another case of plastome downsizing in photosynthetic seed plant lineages.